2011
DOI: 10.1002/jcc.21897
|View full text |Cite
|
Sign up to set email alerts
|

The coupling constant polarizability and hyperpolarizabilty of 1J(NH) in N‐methylacetamide, and its application for the multipole spin–spin coupling constant polarizability/reaction field approach to solvation

Abstract: We present a benchmark study of a combined multipole spin-spin coupling constant (SSCC) polarizability/reaction field (MJP/RF) approach to the calculation of both specific and bulk solvation effects on SSCCs of solvated molecules. The MJP/RF scheme is defined by an expansion of the SSCCs of the solvated molecule in terms of coupling constant dipole and quadrupole polarizabilities and hyperpolarizabilities derived from single molecule ab initio calculations. The solvent electric field and electric field gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…For pedagogical reasons, we will first highlight here the limitation of this gas-phase reference model, that was already mentioned in the literature. 36,57 If the linear proportionality factor g 0 is known, and the same for all molecules, this approach would be very helpful: the liquid first hyperpolarizability depends only on e env . An MD simulation can provide e env for each molecule, and the liquid phase first hyperpolarizability is calculated using eqn (5), so that no expensive QM/MM approach is needed.…”
Section: Using C To Calculate Individual B In Condensed Phasesmentioning
confidence: 99%
See 2 more Smart Citations
“…For pedagogical reasons, we will first highlight here the limitation of this gas-phase reference model, that was already mentioned in the literature. 36,57 If the linear proportionality factor g 0 is known, and the same for all molecules, this approach would be very helpful: the liquid first hyperpolarizability depends only on e env . An MD simulation can provide e env for each molecule, and the liquid phase first hyperpolarizability is calculated using eqn (5), so that no expensive QM/MM approach is needed.…”
Section: Using C To Calculate Individual B In Condensed Phasesmentioning
confidence: 99%
“…Such limitations of perturbation field expansions to model solvation effects had already been discussed in the literature. When studying the nuclear magnetic shielding tensors of the atoms of N-methylacetamide solvated by liquid water, Kjaer et al 36 have shown that the field experienced by the nuclei is very inhomogeneous, so that considering one averaged field from all configurations and/or across all nuclei is not a good approximation. 3.2.2 Separation into short and long-range neighbors.…”
Section: Using C To Calculate Individual B In Condensed Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, we have analyzed the convergence of the calculated value of the pseudo-scalar r ð1Þ I with a hierarchy of Dunning's correlation consistent basis sets for the considered (R)-N-fluor-C-methyl-oxa-aziridine. In Table 1, our results of r ð1Þ I for heavy nuclei 13 C, 14 N, 17 O, and 19 F are shown. We present the paramagnetic, D, and total contributions, which have been computed at the CHF-QR(CTOCD-DZ) level of theory.…”
Section: Full Papermentioning
confidence: 99%
“…The effects of an electric field on NMR spectral parameters have been theoretically determined since some time ago, [3,[6][7][8][9][10][11][12][13][14] either in a purely analytically manner through quadratic response (QR) methods or by numerical differentiation of analytical shielding tensors. Even though there are predominate calculations at the coupled Hartree-Fock (CHF) level, correlation contributions may be important as the nuclear magnetic shieldings are, in many molecules, strongly affected by electron correlation.…”
Section: Introductionmentioning
confidence: 99%